Clinical characteristics and neurophysiology features of amyotrophic lateral sclerosis patients at Sanglah Hospital Denpasar - I Made Odie Lastrawan; Komang Arimbawa; Ni Made Dwita Pratiw (Romanian Journal of Neurology, 2021)
Background. Amyotrophic lateral sclerosis (ALS) is a one of motor neurons disease. The Incidents in Europe are 2.6 per 100,000 people per year and in the United States, more than 5,600 are diagnosed each year. The death was reportedly 2 per 100,000 people per year. In Sanglah Hospital there are no study that described the characteristics clinical and neurophysiology of ALS at Sanglah Hospital. Objective. To find the characteristics of ALS based on clinical and neurophysiology of ALS at Sanglah Hospital in terms of demography, clinical, Nerve Conduction Studies (NCS) and Electromyography (EMG). Methods. Retrospective descriptive study using medical records of patients in neurology polyclinic at Sanglah Hospital from January until December, 2018. Results. From 14 ALS patients with average age of 47 years old, men and women same amount, high school 71.4%, unemployed 50%, and married 92.8%. Symptoms first appeared with an average age of 42 years with complaints of lower limb weakness 64.3%. The diagnosis of ALS with the symptom UMN and LMN on bulbar and 2 spinal region 71.4%, and symptom with the UMN and LMN on 3 spinal region 28.6%. Results of motor and sensory NCS were normal, type axional and mixed neuropathy. Characteristics of EMG were PSW +4, fibrillation +4, MUAP: high amplitude (giant potential), widened duration, polyphasic phase, incomplete IP recruitment in all patients (100%) although in different muscles of the examined patient. Conclusions. Characteristics from 14 patients ALS in 2018 at Sanglah Hospital indicate that patients have a good prognosis.